2016
DOI: 10.1177/2325967116654114
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Time to Recurrence of Instability After Open and Arthroscopic Bankart Repair Techniques

Abstract: Background:The results of open and arthroscopic instability repairs have been shown to be equivalent in recent literature.Purpose:To compare the time to recurrence (TTR) of instability and disease-specific outcome measures in patients undergoing open and arthroscopic Bankart repair.Study Design:Cohort study; Level of evidence, 3.Methods:Patients with recurrent traumatic anterior shoulder instability and a Bankart lesion on diagnostic arthroscopy underwent either open Bankart repair (OB) or arthroscopic Bankart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…Surgical intervention should be completed as quickly as practical once decided upon as the proper course of treatment. Benefits of using an arthroscopic Bankart repair technique include a lower complication rate, smaller incisions, less blood loss, shorter operative times, greater range of shoulder motion postoperatively, less postoperative pain, better cosmesis, less postoperative shoulder stiffness, and fewer wound infections [4,29].…”
Section: Indications/contraindicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical intervention should be completed as quickly as practical once decided upon as the proper course of treatment. Benefits of using an arthroscopic Bankart repair technique include a lower complication rate, smaller incisions, less blood loss, shorter operative times, greater range of shoulder motion postoperatively, less postoperative pain, better cosmesis, less postoperative shoulder stiffness, and fewer wound infections [4,29].…”
Section: Indications/contraindicationsmentioning
confidence: 99%
“…The reported recurrence rate after arthroscopic Bankart repair ranges from 4 to 19% [65]; in newer literature, the risk is increased by participation in contact sports [66]. Additionally, the average amount of time prior to another instability event is less with arthroscopic than open Bankart repair (12.6 versus 34.2 months, respectively) [9]. Patients who desire to return to contact sports should be counseled on the higher recurrent instability rate after arthroscopic repair and weigh this risk against the benefits of this technique, including a faster return to activity, as well as a greater likelihood that they will be able to do so [5].…”
Section: Recurrence Of Shoulder Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Nevertheless, some surgeons continue to favor open Bankart for contact athletes and manual laborers owing to a longer interval to recurrence and a reduced recurrence rate among collision athletes. 7 , 11 , 14 , 18 For patients with a history of failed arthroscopic or open capsulolabral repair or those with clinically significant anterior glenoid bone loss, the Latarjet procedure is considered an excellent option. Notably, recent comparative trials have found that primary Latarjet coracoid transfer may result in a reduced rate of recurrent instability when compared with arthroscopic stabilization.…”
mentioning
confidence: 99%
“…Outras vantagens da artroscopia são a menor perda sanguínea, menor duração da cirurgia e a maior satisfação estética. 12 As taxas de recidivas de luxação após a cirurgia artroscópica vêm diminuindo devido aos avanços tecnológicos e o Quanto à perda de rotação lateral, Bottoni et al 16 demonstraram uma diminuição de 2°a 3°no grupo artroscópico, enquanto, no grupo de cirurgias abertas, houve uma perda de aproximadamente 6,5°da amplitude de movimento. Em nosso estudo, a perda de rotação lateral foi mais observada nos pacientes que apresentavam instabilidade traumática, dado semelhante aos resultados de Ferreira Neto et al, 17 que também encontraram maior limitação da rotação lateral em pacientes com essa característica.…”
Section: Discussionunclassified